The interferon paradox: can inhibiting an antiviral mechanism advance an HIV cure? - Deeks, Steven G. (J Clin Invest, 2016)
While antiretroviral therapy (ART) has improved the quality of life and increased the life span of many HIV-infected individuals, this therapeutic strategy has several limitations, including a lack of efficacy in fully restoring immune function and a requirement for life-long treatment. Two studies in this issue of the JCI use a humanized mouse model and demonstrate that type I interferon (IFN) is induced early during HIV infection and that type I IFN–associated gene signatures persist, even during ART. Importantly, blockade of type I IFN improved immune function, reduced the HIV reservoir, and caused a delay in viral rebound after ART interruption. Together, these two studies support further evaluation of IFN blockade as a supplement to ART.